Pengembangan Media Belajar Matematika “Funmath” di Era Literasi Digital - Tita Tanjung Sari; Anang Hadi Cahyono (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
Corona virus disease 2019 (Covid-19) and its rapid spread pushes all of us to live in a condition known as new normal. The government’s advice to work, study, and pray at home is indeed to creating a new system on the education field in Indonesia. Distance learning becomes an alternative solution to apply during the pandemic. However, there are still many teachers in Indonesia who are not familiar with distance learning sytem, because of implementing the teaching strategies, may be successful with sufficient creativity needed by the teachers to design the learning. In this case, this study aims to develop a mathematics learning media. “FunMath” is developed by using Thiagarajan modification development consisting of define, design, and development. Based on the validation results of media and material experts, the “FunMath” application is feasible with the score of 88.5 for media validation and 95 for material validation. The positive response also comes from the primary school students who completed the questionnaire distributed in Sumenep while learning at home or school with 83.8%, resulting a very good category. “FunMath” is considerably compatible as an alternative to provide ease for teachers, students, and parents, in guiding them to study at home during the pandemic.